Anatomical localization and classification of bundle branch blocks using novel CineECG. (24th May 2021) - Boonstra, MJ; Hilderink, BN; Locati, ET; Asselbergs, FW; Loh, P; Van Dam, PM
Abstract: Funding Acknowledgements: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): This work was supported by the Dutch Heart Foundation Background: Ventricular conduction disorders can induce arrhythmias and impair cardiac function. Bundle branch blocks are diagnosed by 12-lead ECG, but discrimination between complete bundle branch blocks, incomplete bundle branch blocks and normal tracings can be challenging. CineECG computes the mean temporo-spatial isochrone (mTSI) trajectory of activation waveforms in a 3D-heart model from 12-lead ECGs. This trajectory represents the mean trajectory of the ventricular electrical activation at any time interval directly related to ventricular anatomy. In Brugada patients, CineECG has localized the terminal components of ventricular depolarization to right ventricle outflow tract (RVOT). Also, for the localization of bundle branch blocks, the region of latest activation contains the most information. Using CineECG, subject specific anatomically related information about the location of bundle branch blocks is obtained. Purpose: This study aimed at exploring whether CineECG can improve the discrimination between complete left/right bundle branch blocks (LBBB/RBBB), and incomplete RBBB (iRBBB). Methods: We utilized 400 12-lead ECGs from the online Physionet-XL-PTB-Diagnostic ECG Database with a certified ECG diagnosis. The mTSI trajectory was calculated and projected into the anatomical 3D-heart model. Five CineECG classes were established: "Normal", "iRBBB", "RBBB", "LBBB" and "Undetermined", to which each tracing was allocated. We determined the accuracy of CineECG classification with the gold standard diagnosis. Results: A total of 391 ECGs were analyzed (9 ECGs were excluded for noise) and 240/266 were correctly classified as "normal", 14/17 as "iRBBB", 55/55 as "RBBB", 51/51 as "LBBB" and 31 as "undetermined". Average mTSI trajectories were calculated according to ECG diagnosis (Figure). The terminal mTSI contained most information about the BBB localization, as that part directs to the site of latest activation (Figure, red arrow). Conclusion: CineECG provided the anatomical localization of different BBBs and accurately differentiated between normal, LBBB and RBBB, and iRBBB. CineECG may aid clinical diagnostic work-up, potentially also contributing to the difficult discrimination between normal, iRBBB and Brugada patients.